Interval type 2-based hybrid fuzzy evaluation of financial services in E7 economies with DEMATEL-ANP and MOORA methods - Dinçer, Hasan; Yüksel, Serhat; Martinez, Luis (Elsevier Science Bv, 2019)
The financial services are key instrument for the right evolution of economy, mainly in the emerging countries. Therefore, the evaluation of the financial services is crucial for the economic development of such a type of countries. Different methods have been applied to accomplish this service evaluation, but its complexity greatly involves uncertain information. Therefore, this paper aims at considering in a more comprehensive way the managing of such uncertainty by the use of interval type-2 fuzzy sets. Hence, it will be proposed a novel evaluation methodology based on a hybrid multi-criteria decision method integrating DEMATEL-ANP (DANP) and MOORA able to deal with interval type-2 fuzzy sets. For the robustness check, the TOPSIS and VIKOR based on interval type-2 fuzzy sets are compared with the MOORA method and the sensitivity analysis is also applied to analyze the consistency of decision makers' priorities. This novel hybrid methodology will be used to evaluate the financial service performance in the emerging seven (E7) economies to conclude what kind of strategic actions should be taken by governments to improve their financial systems as well as to identify a ranking regarding the financial service quality of the E7 economies.
WOS: 000467687500013
Keywords: Type-2 Fuzzy Sets; Danp; Moora; Topsis; Vikor; Financial Services; E7 Economies